2015
DOI: 10.6113/jpe.2015.15.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Phase Locked Loop based Pulse Density Modulation Scheme for the Power Control of Induction Heating Applications

Abstract: Resonant converters are well suited for induction heating (IH) applications due to their advantages such as efficiency and power density. The control systems of these appliances should provide smooth and wide power control with fewer losses. In this paper, a simple phase locked loop (PLL) based variable duty cycle (VDC) pulse density modulation (PDM) power control scheme for use in class-D inverters for IH loads is proposed. This VDC PDM control method provides a wide power control range. This control scheme a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 20 publications
(18 reference statements)
0
7
0
1
Order By: Relevance
“…The research showed the advantages of implementing a Current Source Parallel Resonant Push-Pull Inverter (CSPRPI) and the possibilities of achieving ZVS with low switching losses. A similar topology based on a half-bridge but a series resonant tank was also proven to have a stable operation at ZVS [24]. Furthermore, the same source proved that these classes of converters can be controlled with a simple phase-locked loop based on a variable duty cycle.…”
Section: Introductionmentioning
confidence: 89%
“…The research showed the advantages of implementing a Current Source Parallel Resonant Push-Pull Inverter (CSPRPI) and the possibilities of achieving ZVS with low switching losses. A similar topology based on a half-bridge but a series resonant tank was also proven to have a stable operation at ZVS [24]. Furthermore, the same source proved that these classes of converters can be controlled with a simple phase-locked loop based on a variable duty cycle.…”
Section: Introductionmentioning
confidence: 89%
“…VCO output signal, the last part of the PLL circuit, and the triangular generator are compared by a comparator to obtain PWM pulses. The PWM signal obtained by the PLL circuit forms the input signal of the PDM control circuit [10,24].…”
Section: Pll Structurementioning
confidence: 99%
“…In these control methods, switching losses and electromagnetic interference (EMI) are quite high and soft switching cannot be performed at all power levels. Pulse density modulation (PDM) is one of the alternative solutions for these problems [23][24][25]. In this study, a PDM control technique based on the principle of deleting some of the switching signals was used in order to enable the system to control the power by providing the soft switching conditions at each power level.…”
Section: Introductionmentioning
confidence: 99%